Dampak Process-Oriented Guided-Inquiry Learning (POGIL) terhadap Pengetahuan Metakognitif Siswa pada Topik Asam-Basa - Ardhana, Ivan Ashif (Hydrogen: Jurnal Kependidikan Kimia, 2020)
Aim of this research is to investigate different impact of Process-Oriented Guided-Inquiry Learning (POGIL) and verification as learning approach at senior high school studentsâ€™ metacognitive knowledge grade XI program IPA on acid-base topic. Research design used was quasi experimental. Hypothesis testing uses t-test with 5% (0,05) significance utilizing SPSS 21 application. Results show that (1) there is significance difference of studentsâ€™ metacognitive knowledge that is taught by POGIL approach and verification, and (2) students that are taught by POGIL approach give better answerâ€™s pattern of declarative,Â procedural, and conditional knowledge than students that are taught by verification approach.